Dietary Compliance Associated with Blood Pressure among Hypertensive Patients - Annisa Latief; Misnati Misnati; Nuryani Nuryani (Journal of Indonesia Applied Nutrition (JIAN), 2026)
Hypertension, a non-communicable disease (NCD), is one of the most serious health issues today and is a major cause of stroke incidents, both systolic and diastolic blood pressure. Factors influencing hypertension include knowledge, dietary compliance, and eating patterns. The study aims to analyze the relationship between knowledge, dietary compliance, and family support with blood pressure in hypertensive patients. The study utilized an analytical survey with a cross-sectional design. The sample size was determined by Slovin formula as many as consisted of 67 hypertensive patients selected using accidental sampling. Data were processed using the chi-square test. The measurement of variable using structured questionnaire. Descriptive analysis revealed the majority nutritional status as normal (58.1%) and overweight (26.9%), the age category 56-65 years old as many as 43.3%, low level of knowledge (28.4%), low dietary compliance (41.8%), and low family support (25.4%). The measurement blood pressure indicated 56.7% of the subject have controlled blood pressure. The research finding revealed that hypertensive patients with knowledge level at good category in 20 (41.7%) and low level of knowledge in 9 (47.3%). Dietary compliance was categorized as compliant in 28 (58.2%) with normal blood pressure and 11 (16.4%) with hypertension, while family support was good 26 (52.0%) with normal blood pressure and 24 (48.0%) with hypertension. The results showed a significant association was found between dietary compliance and blood pressure (p=0.003), but there were not significant assocation between knowledge and family support with blood pressure (p=0.671 and p=0.181), respectively. The study indicated that association between dietary compliance and blood pressure in hypertensive patients. Lifestyle modification strategies should be promoted to maintain long-term dietary compliance among hypertension patients.